Modelling nitrogen and phosphorus cycling and retention in Cyperus papyrus dominated natural wetlands. (December 2019) - Hes, Edwin MA.; van Dam, Anne A.
Abstract: Papyrus ( Cyperus papyrus ) wetlands support millions through food provisioning, which leads to loss of regulating ecosystem services. This study aimed at understanding the impact of changes in water regime and vegetation harvesting on nutrient retention in rooted papyrus wetlands. A simulation model (Papyrus Simulator), developed and calibrated with data from African wetlands, produced reasonable estimates of productivity and nutrient retention. Phosphorus retention was lower than nitrogen retention, leading to a nitrogen-limited environment by reducing the N:P ratio in the water. Absence of surface water during part of the year caused a reduction of biomass. Harvesting increased nitrogen retention from 7% to over 40%, and phosphorus retention from 4% to 40%. Sensitivity analysis revealed assimilation, mortality, decay, re-translocation, nutrient inflow and soil porosity as the most influential factors. Papyrus Simulator is suitable for studying nutrient retention and harvesting in wetlands, and contributes to quantification of ecosystem services and sustainable wetland management. Highlights: Papyrus Simulator is a dynamic simulation model to estimate nutrient retention in rooted Cyperus papyrus dominated wetlands. The model was calibrated with data from selected field studies on Cyperus papyrus dominated wetlands. Simulated biomass and water quality results were within the range of published data from over 40 papyrus wetlands in Africa. The main mechanism for nitrogen and phosphorus retention was peat formation.